The factors affecting learning English as a foreign language at Phoubachieng Upper Secondary School - Luangsombath, Soulichanh; Vongphachanh, Somchith; Phothiladth, Ammalin; Phomphithak, Chansy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Learning factors affecting foreign language learning have an essential influence on students’ achievement in acquiring language. There are many factors that contributed to learning performance such as internal and external factors. Knowledge about learning factors contributes to the understanding of how to manage a suitable classroom environment for foreign language learning. Internal Factors comprising of demotivation, negative attitude, low self-esteem, and motivation, are likely to play a crucial role in students’ language learning accomplishment, while External Factors including lack of school support, unsupportive school environment, and teaching methodology can result in learning performance of students. This study aims at investigating the situations in learning English as a foreign language, factors affecting learning English as a foreign language and how students respond to factors affecting learning English as a foreign language. The study found that most participants at the school were unsatisfied with the provision of facilities. They also mentioned insufficient materials attributed to demotivation in learning. Another factor caused by unsuccessful learning was the school environment. A negative classroom atmosphere contributed to learning. They were less motivated to participate in activity and learning when the instruction was reliant on grammar-translation methods. They revealed the English class was boring because most teachings were reliant on drill, rote, and memorization. They felt demotivated when teaching applied teacher-centered (didactic) methods. The last factor related to the socio-economic statue of family and household responsibility affected their learning. They said they had to spend their time on family more than study.